IMPLEMENTASI SERVICE QUALITY DALAM MENINGKATKAN KEPUASAN PELANGGAN - SUDARJO (AKADEMIKA, 2022)
The purpose of this study is to find out how the implementation and implementation of servicequality in increasing customer satisfaction and to find out how customers' opinions aboutservice quality have been carried out by Radio MAS FM. This research is qualitative research.The results of the research on the implementation of service quality at Radio MAS FM thereare five main dimensions to increase customer satisfaction. Namely tangible physical evidence,reliability, responsiveness, assurance and empathy. These five main dimensions Radio MASFM implements them very well. It can be proven by the results of field interviews withcustomers who use their services. From these five points, MAS FM gets positive responses from its customers from the changing physical evidence of offices, accurate and reliable reliability, fast and precise responsiveness, assurance in instilling customer trust and confidence and empathy given from every employee. Make customers continue to use services and support every program produced by Radio MAS FM and affect customer loyalty indicators regarding Repeat Purchases and Referrals